2021
DOI: 10.3390/min12010034
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Rare Earth Metals (REMs) from Nickel Metal Hydride Batteries of Electric Vehicles

Abstract: Nickel metal hydride (NiMH) batteries are extensively used in the manufacturing of portable electronic devices as well as electric vehicles due to their specific properties including high energy density, precise volume, resistance to overcharge, etc. These NiMH batteries contain significant amounts of rare earth metals (REMs) along with Co and Ni which are discarded due to illegal dumping and improper recycling practices. In view of their strategic, economic, and industrial importance, and to mitigate the dema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Sulphuric acid is one of the most widely used lixiviants used in hydrometallurgical processes for the dissolution of metals from their host materials (minerals) because it is cheap (often produced as a by-product) and can be regenerated. In this Special Issue, Jha et al [18] used the sulphuric acid leaching of rare earth metals (REMs) from end-of-life nickel metal hydride (NiMH) batteries, which are now generated as waste due to their extensive use in the manufacturing of portable electronic devices as well as electric vehicles. The obtained results showed that more than 90% of REMs (Nd, Ce, and La) dissolved when 2 M H 2 SO 4 was used at 75 • C and leached for 60 min in the presence of 10% H 2 O 2 (v/v).…”
Section: Acid Leaching Of Materials and Critical Metals Recoverymentioning
confidence: 99%
“…Sulphuric acid is one of the most widely used lixiviants used in hydrometallurgical processes for the dissolution of metals from their host materials (minerals) because it is cheap (often produced as a by-product) and can be regenerated. In this Special Issue, Jha et al [18] used the sulphuric acid leaching of rare earth metals (REMs) from end-of-life nickel metal hydride (NiMH) batteries, which are now generated as waste due to their extensive use in the manufacturing of portable electronic devices as well as electric vehicles. The obtained results showed that more than 90% of REMs (Nd, Ce, and La) dissolved when 2 M H 2 SO 4 was used at 75 • C and leached for 60 min in the presence of 10% H 2 O 2 (v/v).…”
Section: Acid Leaching Of Materials and Critical Metals Recoverymentioning
confidence: 99%
“…The hydrometallurgical process is more sustainable, selective, and efficient for the recovery of a wide range of products . In this process, waste is dissolved or metals are leached and the metals of interest are extracted/separated from the leachate by different techniques such as precipitation, solvent extraction, electrochemical deposition, adsorption, or a combination of these approaches. , Solvent extraction has been more common owing to its applicability for the recovery of a wide range of metals; however, most solvents have disadvantages such as toxicity, volatility, and flammability, and some of them are difficult to reuse. Previous studies have focused on alternative processes, , and eutectic solvents (ESs) stand out as green alternatives for metal recovery.…”
Section: Introductionmentioning
confidence: 99%
“…These magnets are used in wind turbines, electric vehicle motors, computer hard disk drives, and mobile phones for their excellent magnetic property and high energy efficiency . Pr and Nd are also critical components of mischmetal that is used in nickel metal hydride (NiMH) batteries that are used in some hybrid vehicles, for example, the Toyota Prius …”
Section: Introductionmentioning
confidence: 99%
“…2 Pr and Nd are also critical components of mischmetal that is used in nickel metal hydride (NiMH) batteries that are used in some hybrid vehicles, for example, the Toyota Prius. 5 In the REE industry, the next step after leaching is separation. The separation and purification of REEs involve six steps starting with impurity removal from pregnant leach solution (PLS), followed by mixed REE oxide precipitation using oxalic acid or magnesium carbonate, then solvent extraction to separate individual REEs, followed by precipitation from strip solutions, then calcination to individual REE oxides, and finally metal production using electrolysis or metallothermic methods.…”
Section: Introductionmentioning
confidence: 99%